4+6(x+1)=3x+11+2x

Simple and best practice solution for 4+6(x+1)=3x+11+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+6(x+1)=3x+11+2x equation:


Simplifying
4 + 6(x + 1) = 3x + 11 + 2x

Reorder the terms:
4 + 6(1 + x) = 3x + 11 + 2x
4 + (1 * 6 + x * 6) = 3x + 11 + 2x
4 + (6 + 6x) = 3x + 11 + 2x

Combine like terms: 4 + 6 = 10
10 + 6x = 3x + 11 + 2x

Reorder the terms:
10 + 6x = 11 + 3x + 2x

Combine like terms: 3x + 2x = 5x
10 + 6x = 11 + 5x

Solving
10 + 6x = 11 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
10 + 6x + -5x = 11 + 5x + -5x

Combine like terms: 6x + -5x = 1x
10 + 1x = 11 + 5x + -5x

Combine like terms: 5x + -5x = 0
10 + 1x = 11 + 0
10 + 1x = 11

Add '-10' to each side of the equation.
10 + -10 + 1x = 11 + -10

Combine like terms: 10 + -10 = 0
0 + 1x = 11 + -10
1x = 11 + -10

Combine like terms: 11 + -10 = 1
1x = 1

Divide each side by '1'.
x = 1

Simplifying
x = 1

See similar equations:

| a+(b-c)=0 | | 2(-3-3)=-9 | | S^2+3s=-11 | | 3ln(2x)+1=5 | | 20x+2y=12 | | ln(2x+11)+ln(x-9)-2ln(x)=0 | | 2(-6-3)=-9 | | -6/3=-2 | | 2c+27=5c | | 3a-b-2a+56= | | 2x+3x-3=8 | | .1x+x=3000 | | 9x+45=3(4x-3) | | 5(x-2)+10=5x-25 | | 150a-555= | | 8x+10y=210 | | 3v^3+4v^2+9v+12= | | 1a-46= | | 4=3c-17 | | 2(x-3)=-9 | | a+2a=.08 | | 15/x-2=9/x | | 7x+5=2(3x+12) | | l+4=-2 | | 7(x-2)=3x-2 | | 9-x+8=-6 | | 15=x+12 | | e+-43=-45 | | 4(b-5)+5b(8-6b)= | | 7x+3=2x+58 | | -16(t^2-361)=0 | | 0.3(3n-5)=0.4-0.2(n-7) |

Equations solver categories